PRINSIP PILIHAN HUKUM DALAM PENYELESAIAN SENGKETA PADA KONTRAK E-COMMERCE NASIONAL - HANG BUN; EFRIKO MANURUNG; SAHARA TUA SILABAN; FEBRIANUS GULO (JURNAL ILMIAH KOHESI, 2020)
The existence of e-commerce changed the order of business transactions in Indonesia. E-commerce was born on the demands of the community to fast-paced services easy and practical through the Internet. E-commerce is part of e-business, where e-business coverage is wider, not just business but also involves the collaboration of business partners, customer service, job openings. In addition to the WWW network technology, e-commerce also requires database or database technology, electronic mail (e-mail), and other non-computer technology forms as well as freight systems, and payment tools for electronic trading. There are many advantages gained from ecommerce one of them is selling goods and services products online without having to set up a large store or office as done by offline businesses as a business place. Just by utilizing the Internet network you can already market products or services to consumers anytime and anywhere. Just by using the Internet network you can already market products or services widely to the community. But there is also lack of e-commerce that is expensive cost of making/building an e-commerce system, the level of customer confidence is lacking in e-commerce sites, still not cheap and safe access to the Internet in a particular country. The title in this research study is: "The legal choice principle in dispute resolution on national E-commerce contracts". Problem formulation: How is the dispute resolution process in E-commerce contracts in Indonesia?, how is consumer protection on E-commerce transactions under Law No. 19 of 2016 on electronic information and transactions? This type of research uses normative juridical research and uses primary, secondary, and tertiary data. Data collection using document study methods, all research data already collected, analyzed using descriptive analysis method. The result of this research is the process of dispute resolution on E-commerce contracts in Indonesia, namely with two mechanisms, namely with the path of litigation and nonlitigation. The litigation mechanism is a dispute resolution path through judgment. While non litigation can be done with the path of dispute resolution through arbitration, negotiations, mediation and conciliation. Consumer Protection of E-commerce transactions in Law No. 19 of 2016 on electronic information and transactions is in case of tort conducted by business actors, the right to receive achievement of a number of goods for compensation against tort. This does not apply to Overmacht due to the difficulty of Overmacht proving between business actors and consumers in e-commerce transactions.